Exploring Experiential Learning: Perceptions of Working Postgraduates in Rwanda’s Weekend Mathematics Education Program - Onesme Niyibizi; Marie Claudine Uwitatse (Journal of Research in Mathematics, Science, and Technology Education, 2025)
This study aimed to explore the perceptions and lived experiences of postgraduate students in Rwanda who pursue a Master of Education in Mathematics Education while working full-time, focusing specifically on their engagement in weekend classes. The research sought to understand their motivations, challenges, and outcomes as they uphold the dual responsibilities of professional and academic commitments. Employing a qualitative, phenomenological approach, the study collected data through in-depth interviews with ten postgraduate students. Thematic analysis was used to reveal frequent themes and patterns within their narratives, providing the understanding of their experiences. Findings revealed a different range of motivations powerful these students, including aspirations for career advancement, a desire for personal development, and an interest in gaining specialized knowledge in mathematics education. However, the participants reported significant challenges, with time management and balancing weekend studies with full-time work being among the most prevalent. Despite these difficulties, the students revealed resilience, influencing support systems and intrinsic motivation to manage their commitments. The findings highlighted the unique pressures and demands of weekend postgraduate programs, particularly in balancing professional and personal responsibilities. This study contributes to the growing body of research on the experiences of working postgraduate students. It highlights the importance of made-to-measure program structures and support mechanisms to enhance learning outcomes and improve work-study balance. The insights gained from this research provide valuable implications for educational policymakers, program designers, and institutions offering weekend postgraduate programs, particularly in mathematics education, to better meet the needs of this unique student demographic.